2016
DOI: 10.1016/j.jsbmb.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Age, APOE and sex: Triad of risk of Alzheimer’s disease

Abstract: Age, apolipoprotein E ɛ4 (APOE) and chromosomal sex are well-established risk factors for late-onset Alzheimer’s disease (LOAD; AD). Over 60% of persons with AD harbor at least one APOE-ɛ4 allele. The sex-based prevalence of AD is well documented with over 60% of persons with AD being female. Evidence indicates that the APOE-ɛ4 risk for AD is greater in women than men, which is particularly evident in heterozygous women carrying one APOE-ɛ4 allele. Paradoxically, men homozygous for APOE-ɛ4 are reported to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
419
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 486 publications
(448 citation statements)
references
References 175 publications
(243 reference statements)
19
419
3
7
Order By: Relevance
“…25 Mechanisms that underlie these sex differences may be linked to physiologic changes associated with menopause and estrogen loss that on average begin at 51 years of age 35 just prior to our risk groups. Studies in animals and humans have reported an interaction between APOE ε4, menopause, and cognitive decline (for a review, see reference 36 ). Furthermore, other evidence suggests that carrying one copy of APOE ε4 shifts the age of onset in women, but not in men 18 .…”
Section: Discussionmentioning
confidence: 99%
“…25 Mechanisms that underlie these sex differences may be linked to physiologic changes associated with menopause and estrogen loss that on average begin at 51 years of age 35 just prior to our risk groups. Studies in animals and humans have reported an interaction between APOE ε4, menopause, and cognitive decline (for a review, see reference 36 ). Furthermore, other evidence suggests that carrying one copy of APOE ε4 shifts the age of onset in women, but not in men 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This time limit of proper HRT initiation resulted in introduction of the term the critical window of intervention or the window of opportunity which describes the time after which HRT become worthless. HRT has not the same effect in all genotypes but it is found to be more beneficial in people with APOE2 and APOE3 genotypes than APOE4 [96][97][98][99][100]. At the same time, some studies revealed that the protective effect of HRT against AD is only achieved in long-term users (>10 years), while short-term therapy had no AD preventive actions pointing to the need of long-term HRT use to gain significantly beneficial AD protection [101,102].…”
Section: Sex Hormone Therapy Trials For Alzheimer's Diseasementioning
confidence: 99%
“…Importantly, vascular risk factors including diabetes and hyperlipidemia are additional risk factors for AD (13,14). However, age and the Apo E4 allele continue to be the most significant risk factors for the development of AD along with female sex (15). The greater prevalence of AD in women could be attributed to the higher life expectancy in women, since the incidence of AD in earlier ages is comparable between sexes (16).…”
Section: Etiologymentioning
confidence: 99%